ANALISIS PENGARUH TOTAL ASSET, LABA BERSIH, INFLASI, DAN BI RATE TERHADAP PERGERAKAN HARGA SAHAM: STUDI PADA PERUSAHAAN MANUFAKTUR BEI - Wahyu Ika Kusuma Ningrum (Quantitative Economics Journal, 2017)
This study aimed to test whether the effect of Total Assets, Net Income (Net Revenue), Inflation, and the BI Rate to shares in companies isted on the Stock Exchage in 2005-2014. Another purpose of this study was to see if there is a significant influence on the movement of stock prices BEI manufacturing company to Total Assets, Net Income (Net Revenue), Inflation, and the BI Rate. his research sample is manufacturing companies listed on the Stock Exchange in 2005-2014 and selected by random sampling method. Data used is panel data by type of secondary data collected by the method of documentation. ypothesistesting was conducted using multiple regression analysis as seen from the quared with Eviews program. The results of this study indicate that the Total Assets, Net Income (Net evenue), Inflation, have a significant influence on stocks. While the BI Rate has a significant influence on stock price. This research ontributes to the development of capital markets, especially related to stock price.